Tradisi Bluk Gebluk dan Relasinya dengan Kitab Risalatul Abidin: Studi Historis dan Antropologi Budaya Islam di Genengwaru Pasuruan - Muchammad Lubbil Khobir lubbil; Haikal Ritaj Murghis (UPT Publikasi Ilmiah, 2026)
This study aims to examine the Bluk Gebluk tradition of the community in Genengwaru Village, Rembang Subdistrict, Pasuruan Regency, as well as its connection to the Risalatul Abidin text from the perspectives of Islamic history and culture. This study employs a qualitative approach with a case study design enriched by historical methods, and the data is analyzed using frameworks from Islamic anthropology and cultural sociology. Data collection was conducted through in-depth interviews, participant observation, and documentation. The results indicate that the Bluk Gebluk tradition is a form of cultural da’wah that functions as an effective medium for non-formal Islamic education. The values of aqidah, akhlak, and fiqh are internalized through contextual collective practices in community life. Historically, this tradition reflects the continuity of culture-based da’wah by ulama connected to Islamic literature, particularly the book Risalatul Abidin. Furthermore, this tradition contributes to strengthening social cohesion and shaping the religious character of the community. Despite facing the challenges of modernization, the tradition’s sustainability is supported by the role of religious leaders and its alignment with local culture. Thus, the Bluk Gebluk tradition remains relevant as a model for culture-based Islamic da’wah and education in the contemporary era.